Distinct subsets of retroviruses encode dUTPase. - Elder, J H (1992)
The nonprimate lentiviruses feline immunodeficiency virus, equine infectious anemia virus, visna virus, and caprine encephalitis virus contain a gene segment in the polymerase gene that is lacking in the primate lentiviruses. A related sequence has been noted in other retroviruses, most notably the type D retroviruses. Computer searches have indicated a relatedness between this unique gene segment, termed proteaselike element and elements of both the aspartate proteinase and the dUTPase enzyme families. In this report, we show that members of both nonprimate lentiviruses and type D retroviruses possess dUTPase activity and present a formal demonstration that in feline immunodeficiency virus, the activity is encoded by the proteaselike element.